Using digital short stories in teaching English vocabulary - Zabitgil Gülseren, Özlem; Akar, Sıla Selver; Gülseren, Özlem Zabitgil (St. Kliment Ohridski University Press, 2021)
INTRODUCTION Long-running studies have revealed that modern and authentic methods are substantial means while teaching language. When these methods are combined with technology, they enable acceleration of second language acquisition for language learners. Vocabulary knowledge serves as the cornerstone of all the four language skills: reading, writing, listening and speaking. This research analyses the benefits of digital short story use with a combination of technology and short story approach in language teaching classroom as it shapes the vocabulary knowledge outcomes. “Building up a useful vocabulary is central to the learning of a foreign language” (Cameron, 2001, 72). Vocabulary growth is directly correlated with the four language skills. The more the language learner encounters new vocabulary in meaningful contexts, the stronger their vocabulary development would be. The more vocabulary foreign language learners have, the stronger their communicative powers. With this in mind, promoting vocabulary growth is an important concern for language learners. The digital environment offers rich and authentic visual and auditory input for learners. Literary works comprised of cultural and social details is a noteworthy language model for learners in many ways. Learners are able to examine literary works including syntax discourse functions and correct sentence patterns prevalent in literary texts (Stan, 2014, 454-459) and thus improving their general language capacity in the target language.
Chapter 8 -- Publication date: May 14, 2021 DOI: 10.5281/zenodo.4780891 ISBN: 978-954-07-5203-7 Published in: Developments in Educational Sciences, St. Kliment Ohridski University Press, Sofia, pp. 116-128 (978-954-07-5203-7). Related identifiers: Derived from 978-954-07-5203-7 (ISBN) (Book)